PSYCHOANALYSIS OF MAIN CHARACTER’S IN THE MOVIE SOUL - Davyna Azzahra Putri; Nurul Fadhillah; Muhammad Ilham, (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
This article examined psychoanalysis research into the actions of the main character. The research used data from the 2020 release of the film Soul. The four types of Lacan psychoanalysis—the mirror stage, desire and lack, transference, the real, and the symbolic—were applied in this study as theory concepts in psychology. This study used a qualitative descriptive methodology, focusing on psychoanalysis detail as a classification technique and using librarian research to collect data.